Penentuan tipe sedimen dasar perairan Muara Sungai Banyuasin berdasarkan nilai hambur balik akustik - Ellis N Ningsih; Beta S Barus; Riris Aryawati; Sahrul Ramadhan; Freddy Supriyadi (Faculty of Mathtmatics and Natural Sciences, 2021)
Bottom sediments have an essential role, among others, as a habitat for living things, determining waves, turbidity of the waters, and as information on marine development. Determination of the type of bottom waters can be done using the acoustic method. The use of sound waves in the acoustic method can detect objects in the water column using an echosounder instrument. This research aims to analyze the value of acoustic backscatter in finding the type of sediment at the bottom of the water. This research was carried out in October 2018 - January 2019 in the waters of the Banyuasin River Estuary. The results showed that the sediment base corresponds to the acoustic backscatter value, namely clayey sand with an SS value of -16.23 dB. Clay with SS values ranging from -24.09 dB to -21.29 dB. Muddy clay with SS values ranging from -17.88 dB to -15.54 dB, and sandy clay with an SS value of -16.89 dB. Based on multiple linear regression analysis, the three types of sediment fractions strongly influence the formation of acoustic backscatter by 65.3% or 0.81.